Size measurement based on a two-camera machine vision system for the bayonets of automobile brake pads. (July 2018) - Xiang, Rong; He, Wenhui; Zhang, Xinna; Wang, Dong; Shan, Yuekang
Graphical abstract: Highlights: A size measurement formula for bayonets based on relative measurement was presented. A two-camera machine vision system for the size measurement of bayonets was designed. An automatic ROI setting algorithm for detected edges was designed. It is used for the size measurement of large parts and can achieve high accuracy. Abstract: This paper presents a measurement method based on a two-camera machine vision system and a relative measurement principle to realize the high-accuracy measurement of bayonet sizes of large automobile brake pads. This method used two cameras to capture the local images around the left and right standard edges of a specially designed standard and around the left- and right-detected edges of the measured bayonet. Then, the rectangle regions of the detected edges were set automatically. The measurement equation corresponding to the detected edges was derived after edge detection and linear fitting on the basis of the relative measurement principle. Finally, the bayonet sizes were determined using the measurement equation. Test results showed that repeatability was ±0.019 mm, the average of biases was 0.003 mm and average measurement time was 0.396 s per brake pad, all of which satisfied the requirements of online measurement.